FINTECH SEBAGAI SALAH SATU SOLUSI PEMBIAYAAN BAGI UMKM - Muhamad Rizal; Erna Maulina; Nenden Kostini (Departemen Ilmu Administrasi Bisnis, Fakultas Ilmu Sosial dan Ilmu Politik, UNPAD, 2018)
ABSTRACTIn 2017, more than 40 new fintech businesses is born, this financial business have emerged that have tried their luck in the Indonesian financial landscape along with the other 140s of startup that have stood before. Indonesia's fintech industry has become one of the prima donna that attracted so much attention from the financial industry actors. Investment on startup fintech began to attract a lot of interest, even some startup managed to get series A of investment this year. The fintech sectors are beginning to develop and many new products are launched.Meanwhile, the Ministry of Cooperatives and Small and Medium Enterprises (Ministry of Small and Medium Enterprises) launched 3.79 million micro, small and medium enterprises (SMEs) already utilizing online platform in marketing their products. This number is around 8 percent of the total perpetrators of SMEs in Indonesia, which is 59.2 million.The problem of sources of financing is a classic problem that is a barrier to the growth of SMEs who do not get financing facilities from the banking sector. Lack of financial resources makes SMEs unable to develop innovations to increase production. However, the rapid growth of financing business of fintech, such as peer-to-peer lending can now be another alternative for loan fund raisers. peer-to-peer lending is a financing business that targets the middle to lower market sectors ABSTRAKSepanjang tahun 2017, setidaknya muncul lebih dari 40 bisnis fintech baru yang mencoba peruntungan di lanskap keuangan Indonesia bersama dengan 140-an startup lain yang telah berdiri sebelumnya. Industri fintech Indonesia memang menjadi salah satu primadona yang menarik perhatian begitu besar dari para pelaku industri keuangan. Investasi pada startup fintech mulai banyak diminati, bahkan beberapa startup berhasil mendapatkan investasi seri A di tahun ini. Sektor-sektor fintech mulai berkembang dan produk-produk baru banyak diluncurkan.Sementara itu, Kementerian Koperasi dan Usaha Kecil Menengah (Kemenkop UKM) melansir sebanyak 3,79 juta usaha mikro, kecil, dan menengah (UMKM) sudah memanfaatkan platform online dalam memasarkan produknya. Jumlah ini berkisar 8 persen dari total pelaku UMKM yang ada di Indonesia, yakni 59,2 juta.Masalah sumber pembiayaan merupakan masalah klasik yang menjadi penghambat pertumbuhan UMKM yang tidak mendapat fasilitas pembiayaan dari sektor perbankan. Kurangnya sumber dana menjadikan UMKM tidak dapat mengembangkan inovasi untuk meningkatkan produksinya. Namun demikian pesatnya pertumbuhan bisnis pembiayaan FinTech seperti peer-to-peer lending sekarang ini bisa menjadi alternatif lain bagi para pencari dana pinjaman. peer-to-peer lending merupakan bisnis pembiayaan yang menyasar sektor pasar menengah ke bawah.